Beginning Databases with PostgreSQL 2nd Edition - Matthew, Neil (Apress, 2012)
Welcome to Beginning Databases with PostgreSQL. Early in our careers, we came to recognize the qualities of open-source software. Not only is it often completely free to use, but it can also be of extremely high quality. If you have a problem, you can examine the source code to see how it works. If you find a bug, you can fix it yourself or pass it on to someone else to fix it for you. We have been working with open-source software since 1978 or so, including using the wonderful GNU tools, including GNU Emacs and GCC. We started using Linux in 1993 and have been delighted to be able to create a complete, free computing environment using a Linux kernel and the GNU tools, together with the X Window System, to provide a graphical user interface. PostgreSQL fits beautifully with this, providing an exceptional database system that adheres to the same open-source principles. (For more on open source and the freedom it can bring, please visit http://www.opensource.org.) Databases are remarkably useful things. Many people find a “desktop database” useful for small applications in the office and around the home. Many web sites are data-driven, with content being extracted from databases behind the web server. As databases are becoming ubiquitous, we feel that there is a need for a book that includes some database theory and teaches good practice.